EFEK MODERASI FAKTOR DEMOGRAFIPADA BIAS KEPUTUSANINVESTOR MUDA DI INDONESIA - Tiar Lina Situngkir, _ (2023)
Abstract Tiar Lina Situngkir. Cognitive Bias Factors Affecting Student Group Investment Decisions in Indonesia (Case Study in Indonesia). Doctoral dissertation in Management Science at the Graduate School of the Indonesian University of Education under the guidance of Prof.Dr. H. Nugraha, S. E, M. Si, Akt. CA, CPA, CFA, Prof. H. Dr. Disman, M.S and Dr. Yayat Supriyatna, M.M. The phenomenon of bias results in errors in determining investment decisions. Biased behaviour is an individual psychological view that is not objective in assessing something or available information. This dissertation research uses student research subjects as research subjects. Students are future young investors who are expected to make a major contribution in the investment world on the stock exchange. The dissertation research aims to determine whether cognitive biases affect students in making investment decisions and to determine the influence of demographic factors as research moderation to increase research complexity. Cognitive bias as an independent variable consists of excessive self-confidence, herding behaviour, confirmation bias and dispositional bias. The demographic factors used are religion and gender. The method used in this study is a quantitative method with simple multiple regression analysis techniques and three-way ANOVA. The sample data used in the study were 467 observations. The results of the analysis provide information that there is influence and there is interaction between the independent variables with the main moderation and the second moderation sharpening their influence in determining investment decisions. Dissertation research shows that student investment decisions are proven to be influenced by cognitive biases that are sharpened by interactions with demographic factors. The suggestion from the results of this study is to increase the knowledge of the financial community organized by financial and educational institutions. Government financial institutions such as the Financial Services Authority are more aggressive in providing outreach to the public about the world of finance. Educational institutions play a role by adding a more focused curriculum on the world of behavioural finance to help determine investment decisions that are free from cognitive bias and pay attention to demographic factors that can sharpen investors' mistakes.